Social Distancing to Mitigate COVID-19 Risks Is Associated With COVID-19 Discriminatory Attitudes Among People Living with HIV. Issue 10 (17th September 2020) - Berman, Marcie; Eaton, Lisa A; Watson, Ryan J; Andrepont, J L; Kalichman, Seth
Abstract: Background: Severe acute respiratory syndrome coronavirus-2, the virus that causes COVID-19, is an emerging pandemic with heightened concerns for people with compromised immune systems, including people living with HIV. Purpose: In the absence of a vaccine, public health messaging to mitigate risks for COVID-19 primarily focuses on social distancing. Because people living with HIV commonly experience mistreatment associated with HIV, their response to social distancing may be complicated by psychosocial attitudes associated with COVID-19. Methods: To evaluate these relationships, we conducted a rapid-response, cross-sectional survey with people living with HIV ( N = 149) to assess social distancing practices, COVID-19 discriminatory attitudes, COVID-19 xenophobic attitudes, HIV microaggressions, and concern over contracting COVID-19. Data were collected from participants enrolled in a larger ongoing study between March 30, 2020 and April 17, 2020. Results: Results indicated that choosing to socially distance to reduce COVID-19 exposure was associated with COVID-19 discriminatory attitudes, concerns of contracting COVID-19, and identifying as transgender. Likewise, social distancing imposed by others (e.g., cancelations and restrictions) was associated with concerns of contracting COVID-19. Conclusions: Findings demonstrate that social distancing measures are related to concerns of contracting the virus and discriminatory attitudes toward those who are presumed to be living with COVID-19. These potentially negative psychosocial attitudes toward people perceived to have COVID-19 echo the discriminatory actions and attitudes that we continue to observe in HIV social sciences research. Abstract : Differences in attitudes toward social distancing measures among people living with HIV are mitigated by choosing to socially distance as opposed to having social distancing imposed on them for SARS-CoV-2.